I survived : The battle of D-Day, 1944 - Tarshis, Lauren (Tarshis, Lauren. I survived., 2019)
"When Paul, a French boy living in a Nazi controlled village, finds an American paratrooper in a tree near his home, he has a chance to play a role in the Allies plan to crush the Nazis"--OCLC.